Digital Transformation Strategies to Strengthen Business Resilience in Economic Crisis Situation - Baehaqi Baehaqi; M. Amin; Baiq Rizka Milania Ulfah (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Economic crises pose a significant threat to business continuity, necessitating strategies that strengthen organizational resilience. This study investigates the role of digital transformation in enhancing business resilience during times of economic recession. Through a systematic literature review of scholarly articles, case studies, and industry reports the research covers the retail, service, and manufacturing sectors. Using thematic analysis, key digital strategies were identified and classified. The results indicate that digital transformation strengthens business resilience through operational sustainability, efficiency, customer engagement, and increased adaptability. The retail and service sectors prioritize customer-oriented technologies, while manufacturing focuses on automation. Small and medium-sized enterprises (SMEs) also demonstrate increased resilience despite facing resource constraints. These findings underscore the importance of tailored digital strategies to address economic instability. This study provides a conceptual contribution to digital resilience and offers practical implications for businesses seeking to invest in adaptive and scalable technologies. Further research is recommended to assess long-term impacts and develop industry-specific resilience frameworks.